The roles of microstructure and surface energy on subcritical crack growth in glass-ceramics - Ricco, Pamela [UNESP]; de Carvalho Ramos, Nathália [UNESP]; Bastos Campos, Tiago Moreira; Soares, Viviane Oliveira; de Oliveira Carlos Villas Boas, Mariana; Marques de Melo, Renata [UNESP] (Elsevier, 2021)
This study aimed to investigate the microstructure, failure probabilities, the susceptibility to subcritical crack growth (SCG), and the surface energy of two comercial brands IPS E.max CAD, Ivoclar Vivadent (LD-C) and Celtra DUO, Dentsply (LS-C) and experimental lithium disilicate (LD-E) and metasilicate (LM-E) glass-ceramics. Discs of each material were made to determine the subcritical crack growth parameters and the biaxial flexural strength (ISO 6872). The stresses to failure (MPa) were submitted to Weibull's analysis (CI 95%). The SCG was tested in water at five constant stress rates: 0.005; 0.05; 0.5; 5 and 50 MPa/s. By measuring the contact angles of water and diiodomethane on the glass-ceramics, we calculated the surface energy (mN/m). The characteristic strengths (MPa) and the Weibull moduli were 382.8 ± 8.3 and 10.1 ± 1.5, 148.5 ± 4.0 and 8.4 ± 0.8, 233.5 ± 10.4 and 5 ± 0.6, and 280.4 ± 9.1 and 6.8 ± 0.9 for LD-C, LS-C, LD-E and LM-E, respectively. The parameter of susceptibility to SCG (n) was: LD-C (18.2 ± 2.5), LS-C (25.6 ± 5.8), LD-E (23.2 ± 8.1), and the LM-E (15.1 ± 2.1). The polar and dispersive energy of LD-C was (~45) and (~26) respectively. The microstructures show that the commercial glass-ceramics are more refined and uniform than the experimental ones, which led to less strength variation. The stress corrosion cracking of the glass-ceramics, mainly LD-C, seemed to be a combination of the surface energy and microstructural features.
Keywords: Ceramic; Crack; Fracture